Категорії для розуміння індивідуальності в архітектурі - Смалійчук, Анатолій; Каушанський, Олександр; Smaliychuk, Anatoly; Kaushanskiy, Oleksandr (Видавництво Львівської політехніки, 2020)
Індивідуальність в творчості є однією з головних засад. Незважаючи на це, розуміння необхідності дослідження є недостатнім. Ця категорія поєднує в собі, як теорію, так і практику. Зважаючи на складність смислової природи індивідуальності, її можна окреслити через інші архітектурно-смислові поняття і субстанції – норму, масштаб, стиль, тип, ідентичність, межу, метод.

Individualism in creativity is one of foundation. Nevertheless that understanding of creativity neediness is deficient today. The category combine, as theory and practice by itself. For identifying individuality, we can use such architectural categories as style, boundary, norm, scale, and fundamental philosophical category as character, identity, method, phenomenon. The problem was researched theorist of architecture O. Rapparot in the context of individuality, creativity and identity. Individuality have multiply nature, that is necessary to fit it connection with, architectural fundamental categories. Temporal context and prevailing style is also worth to consideration. No less important factor influencing of economic to it nowadays. Economic, more precisely the price often acts as a determinant. Considering the complexity of this concept, it is nesecity to define boundaries of individuality. We can divide the Individuality into deep and superficial. Deep individuality is always multiple and generated by many factors with complexity of their relationships. Superficial individuality rather easy to understand, often generated by artistic or compositional factors as usual. Individuality relates to design and architecture in different way. Individuality, as an architecture is generated by uniqueness. It is often the basis of identity, a fundamental category in philosophical discourse. Concept of typology can be a points of connection between architecture and individuality. Concept of individuality have phenomenological nature. We must know about it. Therefore, category of norm can often conflict with individuality, because they have very different foundation. The scale can determinate the borders of individuality. Technology, method and fashion can expand or straiten possibilities for individuality in architecture.
Categories for understanding individuality in architecture
Keywords: індивідуальність; стиль; норма; масштаб; контекст; творчість; norm; scale; style type; identity; boundary; method; 72.01; 159.954